Analysis of the maturity level of social media in msmes using the social strategy cone approach - Sadikin, Abdurrahman; Mokodompit, Eliyanti Agus; Astuti, Rini Puji; Indriana, Intan Hesti; Kraugusteeliana, Kraugusteeliana (Jurnal Ekonomi, 2024)
Using the social strategy cone approach, this study examines how well MSMEs operating online cake shops perform in terms of understanding social media maturity. According to the analysis, the majority of businesses have been effective in identifying the preferences and inclinations of their target market, but they still struggle with social media monitoring and assessment. To detect shifting trends and client needs more quickly, enhanced assessment and monitoring tools are required. 15 MSMEs respondent had exceptional social media strategy maturity, compared to six good, two fair, and one poor, according to the data. There were notable distinctions in the evaluation results: the target audience's preferences and interests were best understood, while monitoring and evaluation received the lowest scores. The stages for improvement include active customer interaction, quick response to changes in the social media landscape, and review through medical analysis of social insights and reports